A real-time virtual outing using virtual reality for a hospitalized terminal cancer patient who has difficulty going out: a case report - Niki, Kazuyuki; Egashira, Satomi; Okamoto, Yoshiaki (Frontiers in Virtual Reality, 2024)
Objective Even if hospitalized terminal cancer patients wish to go out, it is sometimes difficult for them to realize this because of various symptoms. We have been providing a virtual outing experience using virtual reality (VR) for terminal cancer patients who have difficulty going out, and have often received requests to "talk with people in the virtual outing," but there is a problem that a large time lag occurs in conversation in a VR space under the general Internet environment. However, with the advent of systems that enable high-speed, low-latency communications, real-time communication is now possible even in VR spaces. Thus, we aimed to explore the feasibility of implementing the real-time virtual outing.. Methods The patient's preferred virtual outing was to his daughter's new home. The study operator used a 360° video real-time sharing system to broadcast the view of the daughter's home. The patient experienced the images using a VR head-mounted display in his room. The patient's wife, son, daughter, and grandson participated in this delivery using a laptop computer from a dayroom in the hospital, and his daughter's husband participated using the 360° video real-time sharing system from the daughter's home with the researcher. Before and after the virtual outing, changes in symptoms and emotions were assessed using the Edmonton Symptom Assessment System Revised Japanese version and the Numerical Rating Scale for headache, dizziness, pleasure, and satisfaction. In addition, we collected the patients' impressions of the virtual outing. Results The patient was a male in his early 70s. After approximately 30 minutes of real-time virtual outings, "tiredness, drowsiness, depression, and well-being" were improved and "pleasure, and satisfaction" were increased, while no side effects or worsening of symptoms were observed. In addition, it was observed from the patient's comments that he felt a sense of presence, as if he were her home.. Discussion The patient and his family could enjoy smooth conversation without time lag even in the VR space. Therefore, it was suggested that real-time virtual outings using VR could help realize the wishes of hospitalized terminal cancer patients who have difficulty going out as a new approach.